Jezus Janowy jako objawiciel oblicza Ojca - Wróbel, Mirosław S. (Verbum Vitae, 2011)
The present article deals with the essential message of the Fourth Gospel which is based on the relation between Father and Son. The main motive of this article is the last verse of the Prologue (Jn 1:18) which appears like leitmotive in the various contexts of the Gospel of John. In the first part of the article the author describes the relation between Father and Son in the Fourth Gospel. He stresses especially a deep communion between them which determines the function of Son as the Revealer of His Father. In the second part of the article the author makes analysis on the function of Jesus as the Revealer of Father. This function can be seen especially in His words and acts. The main goal of this function is the faith of the Jesus’ disciples in God who is the loving Father and Donor of salvation. In the power of faith every human being can recognize in Jesus the face of Father whose main feature is Love until the mystery of the Cross.